THE RELATIONSHIP BETWEEN ELECTRONIC WORD-OF-MOUTH AND GEN Z CONSUMERS' INTENTION IN SELECTING EATING PLACE IN HO CHI MINH CITY, VIETNAM - Nguyen Phuc HUNG*; Do Le Phuc Hung THINH (Geo Journal of Tourism and Geosites)
Electronic Word of Mouth (eWOM) is one of the prevalent forms of information interaction activities in the era of digital technology. In the F&B field, it can be understood as the method by which consumers share information, experiences and reviews about the products and services from individuals or businesses through various online channels such as social media, forums, personal blogs and other platforms. Reflecting current trends, this research aims to examine the factors and t he extent to which eWOM influences the behaviour of Generation Z consumers in Ho Chi Minh City. The res earch methods employed include qualitative and quantitative approaches, serving the purpose of literature review, statistical data analysis and structural equation modelling to assess the relationship between eWOM and the decision-making process in choosing eating places. The study reveals that four factors, namely information quality, information credibility, relevance of information and attitude towards information, directly impact the acceptance of eWOM information, subsequently influencing the intention selection of Gen Z consumers in Ho Chi Minh City. Additionally, brand trust is identified as a positive factor in this research relationship. The findings provide valuable insights into the role of eWOM in the intention selection of Gen Z consumers. This information can be applied by managers and marketers to develop more intelligent management and marketing strategies in Ho Chi Minh City, providing a competitive advantage for businesses.